Women's employment exits in Egypt: the roles of marriage, children, job characteristics, and women's empowerment. Issue 2 (3rd July 2022) - Ehab, Maye
ABSTRACT: Transition to non-employment is prevalent for women in the Egyptian labor market, particularly those working in the private sector. This paper analyzes women's labor market transitions, particularly to non-employment and to other labor market states in the time around marriage and childbirth. We test whether individual characteristics, work characteristics, or agency affect women's transitions. Specifically, the paper answers three main questions: First, what are the explanatory factors for the women's transition to non-employment? Second, what are the differences between the effect of previous job characteristics and women's agency on the employment decision? Third, what are the determinants of the transition to other labor market states (multiple employment decisions)? Drawing on panel and retrospective data from the 2012 and 2018 waves of Egypt's Labor Market Panel Survey, we estimate these relationships using a single risk model and a competing risk model. Results show that marriage and motherhood increase women's transition to non-employment. The timing of the transition happens at marriage and the year before marriage (anticipation effect). This impact is more considerable for women working in the private sector than the public sector. Women working in non-wage work transition to private wage work in the years before marriage. The results show that the sector of employment plays a crucial role in women's transition to non-employment. In addition, the availability of external help in the household is considered an important factor that can help retain women in the labor force.